Dampak Perubahan Iklim Terhadap Produktivitas Tanaman Jeruk (Citrus sp) Di Kota Batu - Deslyati Putri Br Sitepu; Sisca Fajriani; Roedy Sulistyono (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Climate change is one of the most important problems today because it affects the agricultural sector which results in decreased production of food crops, both vegetables and fruits. Citrus is one of the leading horticultural commodities and has a demand that tends to increase in 2015 - 2017, namely 22,772 tons, 23,827 tons and 26,313 tons per year. The aim of this research is to find out the effect of climate change on the productivity of citrus Batu 55 and to get the climatic elements that most influence the productivity of citrus Batu 55. The research was conducted from February 2020 to May 2020 in Batu City. Climate change in Batu city affects the peroduktivitas of Tangerine Stone 55 with a correlation value of 0.011. The most influential climate element to the productivity of Batu 55 Citrus is rainfall with multiple linear regression equations as follows: : Y = -7,212 + 0.741 X1 + 0.686 X2 + 0.119 X3. Based on the equation, rainfall variables have a regression coefficient value of 0.741, a variable regression coefficient of wind speed of 0.686 and a temperature variable regression coefficient value of 0.119.